Cleavage and reassembly C≡C bonds of ynones to access highly functionalized ketones - Rong, Jiaxin (2022)
An economical strategy has been designed to formally cleave CC bonds of ynones through copper-catalyzed carbene chemistry. It proceeds under mild reaction conditions in a step-economy process by simultaneously cleaving the CC bonds and constructing C-C bonds. Depending on the substitution of the ynones, the reactions can proceed efficiently to generate synthetically useful 1,4-ketoaldehydes and cyclopentenone compounds. A plausible pathway is proposed that involves an active cyclopropane intermediate that consequently undergoes a cascade ring-opening reaction. The method works for a spectrum of ynones and N-tosylhydrazones that give good to excellent yields using a cheap copper catalytic system.